Assessment for bone health in patients with differentiated thyroid carcinoma after postoperative thyroid-stimulating hormone suppression therapy: a new fracture risk assessment algorithm - Jia, Huiran; Qu, Wei; Cai, Xiaoting; Li, Meiye; Qian, Ying; Jiang, Zhaoshun; Zhang, Zongjing (Frontiers in Endocrinology, 2023)
Purpose: The fracture risk assessment tool (FRAX) is used to assess the 10-year risk of major site and hip fractures; however, whether this tool can be applied to patients receiving levothyroxine-based thyroid-stimulating hormone (TSH) suppressive therapy for postoperative differentiated thyroid cancer (DTC) patients is yet to be clarified. Methods and Design: A total of 64 patients with DTC following thyroidectomy and oral levothyroxine for TSH suppression therapy and 30 gender- and age-matched controls were collected. The fracture risk was compared between the affected groups with different TSH levels. FRAX was used to calculate the fracture risk with and without bone mineral density (BMD). The TSH level was converted to an age-weighted score to estimate the fracture risk of postoperative differentiated thyroid cancer patients. The sensitivity, specificity and area under the AUC curve of the traditional FRAX and the new algorithm for osteoporosis diagnosis were compared. Dual-energy X-ray bone mineral density measurement T score was used as the gold standard to diagnose osteoporosis. Results: There were 24 patients in the T ≥ -1-2.5 group, 23 in the -2.5 < T < -1 group, and 17 in the T ≤ -2.5 group. The T score of BMD in the disease group was significantly lower than that in the control group (P < 0.05). The risk of MOF and hip fracture without T score were significantly different under various TSH levels (p < 0.05). The area under the curve (AUC) of FRAX without BMD for predicting major osteoporotic fractures (PMOF) and predicting major hip fractures (PHF)was 0.694 and 0.683, respectively. The cutoff values were 2.15% and 0.25%, respectively. The AUC of FRAX with BMD for PMOF and PHF was 0.976 and 0.989, respectively, and the cutoff values were 4.15% and 1.1%, respectively. The AUC of FRAX without BMD for PMOF and PHF was 0.708 and 0.72, respectively, and the cutoff values were 5.5% and 1.55%, respectively. Conclusions: FRAX is suitable for postoperative DTC patients after TSH suppressive therapy. In the absence of BMD, TSH weighted by age can improve the specificity of FRAX in the diagnosis of osteoporosis in this population.